Measurement of unsteady fluid force acting on limbs in swimming using a robot arm and its modeling using the Swimming Human Simulation Model "SWUM" - Nakashima, M.; Takahashi, A. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Thrust generated by the limbs is one of the most important issues in the biomechanics of swimming. Many studies to date have been conducted in order to investigate the fluid force acting on the limbs, especially for the hand, by experiments and numerical simulations. However, most of them were confined to the steady condition although the swimming motion is completely unsteady. Some recent studies have conducted experiments and simulations for unsteady motion. However, such studies have investigated the unsteady motion only in one or two degrees-of-freedom (DOF), which are still far away from the real swimming motion. Therefore, the objective of this study was to investigate the unsteady fluid force during swimming in more realistic situation. For this objective, a robot arm which can perform 5DOF motion, and can represent both the upper and lower limb motions during swimming was developed. METHODS: The joint torques and the resultant thrust acting on the robot arm were measured by the force sensors attached to the robot. In a circulating water tank, an experiment to measure the fluid force was conducted for four swimming strokes of the upper and lower limbs. In order to model the unsteady fluid forces, the swimming human simulation model "SWUM", which has been developed by the authors (Nakashima et al., 2007), was employed. RESULTS: AND DISCUSSION: From the experiment, it was found that even the slight difference of the fluid forces between slightly different swimming motions can be quantified by the developed experimental system. The measured thrust of the crawl stroke reached the maximum value of 50N. With respect to the modeling, fluid force coefficients, which are the parameters in the fluid force model, were identified using optimizing calculation, so that the discrepancy of the forces and moments between the experiment and simulation was minimized. Good agreement between the experiment and simulation with the determined fluid force model indicated validity of the determined model. The averaged discrepancy between the simulation and experiment was 11%. The identified fluid model will be useful for mechanical analyses of various swimming motions by SWUM in the future studies.